2019
DOI: 10.1007/s00027-019-0662-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-conservative patterns of dissolved organic matter degradation when and where lake water mixes

Abstract: In this study, we experimentally investigated the degradation of dissolved organic matter (DOM) during lateral and vertical mixing of different water masses in a peri-alpine lake. River intrusions and vertical winter turnover in Lake Geneva (Switzerland, France) were simulated through short-term laboratory incubations by mixing riverine and lacustrine waters or lacustrine waters collected at different depths in winter. Dissolved organic carbon (DOC) degradation was monitored by dissolved oxygen (DO) measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 72 publications
5
7
0
Order By: Relevance
“…Consequently, it has been determined that even these blends have a rate of biodegradation reduced under composting conditions, and under anaerobic digestion (Camacho‐Muñoz et al., 2020). Similar behaviors have been reported in mixtures based on PLA/PHB/ATBC (Lemos Machado et al., 2017) and PLA/PHB/PEG (Lambert & Perga, 2019; Lambert & Wagner, 2017) under the same disintegration conditions. In these studies, it has been reported that PHB slightly inhibits the degradation of PLA evaluated under the ISO 20200 standard.…”
Section: Resultssupporting
confidence: 81%
“…Consequently, it has been determined that even these blends have a rate of biodegradation reduced under composting conditions, and under anaerobic digestion (Camacho‐Muñoz et al., 2020). Similar behaviors have been reported in mixtures based on PLA/PHB/ATBC (Lemos Machado et al., 2017) and PLA/PHB/PEG (Lambert & Perga, 2019; Lambert & Wagner, 2017) under the same disintegration conditions. In these studies, it has been reported that PHB slightly inhibits the degradation of PLA evaluated under the ISO 20200 standard.…”
Section: Resultssupporting
confidence: 81%
“…Several models can be used to characterize DOM degradation kinetic. Here we applied a first-order exponential decay model in order to derive a decay constant describing the overall dynamic of DOM degradation (Lambert and Perga, 2019;Lu et al, 2013;Shang et al, 2018) as well as the size of the short-and a long-term reactive carbon pools (STRC and LTRC, respectively). Decreasing DOC concentrations during the incubations were modeled using GraphPad Prism 8 software according to the following equation:…”
Section: Characterization Of Dom Degradation Kineticsmentioning
confidence: 99%
“…An alternative scenario would be that the release of simple and labile organic compounds derived from autochthonous sources enhances the degradation of terrestrial aromatic DOM by the so-called priming effect (Bianchi, 2011), inducing a final net increase of C emitted to the atmosphere. The priming effect is a process through which labile pool of DOM can enhance ("prime") the degradation of a more recalcitrant DOM pool based on interactions between microbial communities and/or changes in their functions (Guenet et al, 2010;Kuzyakov et al, 2000), but its occurrence in aquatic ecosystems is highly debated (Attermeyer et al, 2014;Bengtsson et al, 2018;Lambert and Perga, 2019). To determine how human activities may impact the mineralization of terrestrial DOM and infer the consequence on the active role of inland waters into the global C cycle, it is therefore necessary to evaluate the consequences on DOM sources, composition, but also DOM bioavailability and to identify which fraction of the DOM pool fuels respiration.…”
Section: Introductionmentioning
confidence: 99%
“…A load of dissolved organic material in aquatic ecosystems is a combination of various organic compounds originating from the catchment area (allochthonous material) and the results of the primary production and decomposition process in the waters (autochthonous). During the fluvial flow, organic matter movements undergo a microbiologically continuous process and contribute to the ecological and biochemical condition [18]. The COD reflects the level of organic pollution in the waters and is associated with domestic pollutants, mainly from the catchment area.…”
Section: B Impact Of Pollutant Loadsmentioning
confidence: 99%